Protolith age of Santa Maria Chico granulites dated on zircons from an associated amphibolite-facies granodiorite in southernmost Brazil - Hartmann,Léo A. (2008)
U-Pb dating of zircon was undertaken with the Beijing SHRIMP II (sensitive high resolution ion microprobe) on anamphibolite facies granodiorite and an almandine-albite granulite from the Santa Maria Chico Granulitic Complex, southern Brazilian Shield. This work was also done to unravel protolith ages which are often hidden in the array of partly reset data. The obtained metamorphic ages of the granodiorite gneiss and the granulite are 2035 ± 9 Ma and 2006 ± 3 Ma, respectively. These data are within the range of metamorphic ages determined in previous studies (2022 ± 18 Ma and 2031 ± 40 Ma). However, protolith ages for the granodiorite (2366 ± 8 Ma) and the granulite (2489 ± 6 Ma) were obtained which are outside the previously recognized range (> 2510-2555 Ma). The magmatic protolith age of the granodiorite refers to a previously little known magmatic event in the shield. Further investigations may demonstrate that amphibolite facies zircon crystals are useful as a window into geological events in associated granulites, because zircon ages are blurred in the studied granulites.